The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/00016340500290947
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and major morbidity in premature infants less than 31 weeks gestational age in the decade after introduction of surfactant

Abstract: Despite changes in obstetric and neonatal care during the 1990s, mortality and major morbidity rates did not change significantly after the introduction of surfactant in 1991. Comparison of local, regional, national, and international mortality and morbidity rates are becoming more important in allocating resources and in decision-making at the limits of viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Validity of Dexamethasone use in advanced and severe ROP seems to be confirmed by hypothesis including the presence of proinflammatory agents in the development of retinal abnormalities. It is proved by the increased level of CRP in the analyzed laser-steroids group (p<0.01), being the highest in the most advanced ROP stages, coexisting with intrauterine infection, enterocolitis necroticans and pneumonia [2][3][4][5]7]. Moreover, in this group the significant increase of transfusion number, prolonged duration of ventilation and anemia was noticed (p<0.01), which is in accordance with data in the literature [45].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Validity of Dexamethasone use in advanced and severe ROP seems to be confirmed by hypothesis including the presence of proinflammatory agents in the development of retinal abnormalities. It is proved by the increased level of CRP in the analyzed laser-steroids group (p<0.01), being the highest in the most advanced ROP stages, coexisting with intrauterine infection, enterocolitis necroticans and pneumonia [2][3][4][5]7]. Moreover, in this group the significant increase of transfusion number, prolonged duration of ventilation and anemia was noticed (p<0.01), which is in accordance with data in the literature [45].…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, it has been revealed that the so-called Fetal Inflammatory Response (FIRS) is the result of chorioamnionitis, antenatal intrauterine as well as Candida infections which are important agents in pathogenesis of prematurity complications such as sepsis, Periventricular Leukomalacia (PVL), Intraventricular Hemorrhage (IVH), Necrotizing Enterocolitis (NEC) or bronchopulmonary dysplasia [2,3,5,6]. There are also studies which state that the abovementioned factors intensify frequency and severity of ROP, however neonatal noninfectious inflammation might further increase the inflammatory burden [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that worldwide, over 1 million neonates die annually due to overwhelming infections [1]. The incidence of sepsis correlates inversely with the gestational age of the infants, and premature infants, in particular, show a unique susceptibility to (bacterial) pathogens with secondary sepsis rates ranging from 22% to 36% in very low birth-weight neonates and up to 62% in extremely premature infants [2][3][4]. In addition to extrinsic factors, such as invasive procedures and long hospital stays, an immaturity of the immune system is thought to account for the increased rate of neonatal infections [5].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of factors such as regionalization of perinatal care, more widespread use of antenatal steroids, postnatal surfactant, new modalities of mechanical ventilation and therapeutic use of nitric oxide, prevention of streptococcus group B infection, improvement of nutrition and improvement of general care in the NICU have undoubtedly contributed significantly to reducing neonatal mortality in ELBW neonates [18] . However, mortality in the delivery room (DR) has not substantially changed in the last decade and still represents 15% of liveborn and 32% of total deaths of ELBW infants [17,[19][20][21][22] . Interestingly, factors influencing early death in the DR are related with a proactive or a restrictive approach to ante-and perinatal treatment of the most immature infants between 22 and 25 weeks' gestation [23,24] but also to improving resuscitation protocols by implementation of acquired knowledge in everyday practice [25] .…”
Section: Early Neonatal Mortalitymentioning
confidence: 99%